2020
DOI: 10.5194/gmd-13-977-2020
|View full text |Cite
|
Sign up to set email alerts
|

Beijing Climate Center Earth System Model version 1 (BCC-ESM1): model description and evaluation of aerosol simulations

Abstract: Abstract. The Beijing Climate Center Earth System Model version 1 (BCC-ESM1) is the first version of a fully coupled Earth system model with interactive atmospheric chemistry and aerosols developed by the Beijing Climate Center, China Meteorological Administration. Major aerosol species (including sulfate, organic carbon, black carbon, dust, and sea salt) and greenhouse gases are interactively simulated with a whole panoply of processes controlling emission, transport, gas-phase chemical reactions, secondary a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 77 publications
(116 reference statements)
0
31
0
Order By: Relevance
“…Overall, nine coupled ocean-atmosphere climate models performed the SSP3-7.0 and SSP3-7.0-lowNTCF simulations, including CNRM-ESM2-1 (Séférian et al, 2019;Michou et al, 2019), MIROC6 (Takemura et al, 2005(Takemura et al, , 2009Tatebe et al, 2019), MPI-ESM1-2-HAM (Mauritsen et al, 2019;Neubauer et al, 2019;Tegen et al, 2019), NorESM2-LM (Seland et al, 2020), BCC-ESM1 (Wu et al, 2019(Wu et al, , 2020, GFDL-ESM4 (John et al, 2018;Horowitz et al, 2018;Dunne et al, 2020;Horowitz et al, 2020), CESM2-WACCM (Emmons et al, 2020;Gettelman et al, 2019;Tilmes et al, 2019), UKESM1-0-LL (Sellar et al, 2019), and MRI-ESM2-0 (Yukimoto et al, 2019). However, the first four models (CNRM-ESM2-1, MIROC6, MPI-ESM1-2-HAM, NorESM2-LM) lack interactive tropospheric chemistry schemes and therefore include identical ozone evolution in both SSP3-7.0 and SSP3-7.0-lowNTCF simulations (as recommended by AerChemMIP).…”
Section: Aerchemmip Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, nine coupled ocean-atmosphere climate models performed the SSP3-7.0 and SSP3-7.0-lowNTCF simulations, including CNRM-ESM2-1 (Séférian et al, 2019;Michou et al, 2019), MIROC6 (Takemura et al, 2005(Takemura et al, , 2009Tatebe et al, 2019), MPI-ESM1-2-HAM (Mauritsen et al, 2019;Neubauer et al, 2019;Tegen et al, 2019), NorESM2-LM (Seland et al, 2020), BCC-ESM1 (Wu et al, 2019(Wu et al, , 2020, GFDL-ESM4 (John et al, 2018;Horowitz et al, 2018;Dunne et al, 2020;Horowitz et al, 2020), CESM2-WACCM (Emmons et al, 2020;Gettelman et al, 2019;Tilmes et al, 2019), UKESM1-0-LL (Sellar et al, 2019), and MRI-ESM2-0 (Yukimoto et al, 2019). However, the first four models (CNRM-ESM2-1, MIROC6, MPI-ESM1-2-HAM, NorESM2-LM) lack interactive tropospheric chemistry schemes and therefore include identical ozone evolution in both SSP3-7.0 and SSP3-7.0-lowNTCF simulations (as recommended by AerChemMIP).…”
Section: Aerchemmip Modelsmentioning
confidence: 99%
“…Furthermore, studies show that the hemispheric contrast in aerosol forcing has shifted the tropical rainbelt southward, which is associated with a weakening of the west African monsoon and the occurrence of the Sahel drought of the mid-1980s (Rotstayn and Lohmann, 2002;Biasutti and Giannini, 2006;Allen and Sherwood, 2011;Ackerley et al, 2011;Chang et al, 2011;Biasutti, 2013;Hwang et al, 2013;Dong et al, 2014;Allen et al, 2015;Undorf et al, 2018). The observed precipitation decrease during recent decades over most of the areas affected by the south and east Asian monsoon can also be explained by the dominance of aerosol radiative effects suppressing precipitation over the expected precipitation enhancement due to increased GHGs (Wang et al, 2013;Song et al, 2014;Li et al, 2015;Xie et al, 2016;Krishnan et al, 2016;Guo et al, 2016;Lau and Kim, 2017;Zhang et al, 2017;Lin et al, 2018;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…CC BY 4.0 License. relevant publications (Wu et al, 2008(Wu et al, , 2010Wu, 2012;Wu et al, 2013;Lu et al, 2013;Wu et al, 2019;Lu et al, 2020a;Wu et al, 2020). The dynamic core in BCC-AGCM3-MR uses the spectral framework as described in Wu et al (2008), in which explicit time difference scheme is applied to vorticity equation, semi-implicit time difference scheme for divergence, temperature, and surface pressure equations, and semi-Lagrangian tracer transport scheme is used for water vapor, liquid cloud water and ice cloud water.…”
Section: Atmosphere Modelmentioning
confidence: 99%
“…The dynamic core in BCC-AGCM3-MR uses the spectral framework as described in Wu et al (2008), in which explicit time difference scheme is applied to vorticity equation, semi-implicit time difference scheme for divergence, temperature, and surface pressure equations, and semi-Lagrangian tracer transport scheme is used for water vapor, liquid cloud water and ice cloud water. The main model physics in BCC-AGCM3-MR was described in Wu et al (2019), which includes the modified scheme of deep convection suggested by Wu (2012), a new diagnostic scheme of cloud amount (Wu et al, 2019), shallow convection transport scheme (Hack, 1994), the stratiform cloud microphysics followed the framework of non-convective cloud processes in NCAR Community Atmosphere Model version 3 (CAM3, Collins et al, 2004) but a noticeable treatment for indirect effects of aerosols through mechanisms of clouds and precipitation, the radiative transfer parameterization that originally implemented in CAM3, a modified boundary layer turbulence parameterization based on the eddy diffusivity approach (Holtslag and Boville, 1993), and treatments of gravity waves that are generated by a variety of sources including orography and convection (Lu et al, 2020a).…”
Section: Atmosphere Modelmentioning
confidence: 99%
See 1 more Smart Citation